2013
DOI: 10.1161/circheartfailure.112.000089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renal Tubular Damage, as Assessed by Urinary β 2 –Microglobulin–Creatinine Ratio, on Cardiac Prognosis in Patients With Chronic Heart Failure

Abstract: The online-only Data Supplement is available at http://circheartfailure.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…This was a prospective observational study to elucidate the clinical importance of RTD in patients with CHF [11,14]. We included 456 patients who were admitted to our hospital for the diagnosis or treatment of CHF between 2009 and 2013.…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a prospective observational study to elucidate the clinical importance of RTD in patients with CHF [11,14]. We included 456 patients who were admitted to our hospital for the diagnosis or treatment of CHF between 2009 and 2013.…”
Section: Study Subjectsmentioning
confidence: 99%
“…RTD-UBCR was defined as a UBCR C 300 lg/g (log 10 UBCR C 2.47 lg/g), as previously reported [11,14]. RTD-NAG was defined as a NAG C 14.2 U/g, according to previous report [13].…”
Section: Biochemical Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…During an episode of acute decompensation, increased glomerular pressure may cause proteinuria. In a recent observational study, patients with acute decompensated heart failure were found to have increased urinary albumin excretion that resolved or decreased significantly with standard heart failure treatment [18]. Although diabetes is known to play an important role in the pathogenesis of many glomerular diseases, glomerular damage was not closely related to the presence of diabetes in our patients.…”
Section: Discussionmentioning
confidence: 68%
“…The aim of the present investigation was to assess patients with CRS-2 for the presence of glomerular damage during an episode of acute cardiac decompensation, owing to its temporal association with increased urinary albumin excretion [18]. The presence of glomerular damage was assessed by quantification of urinary podocyte-specific peptides by liquid chromatography (LC) coupled to tandem mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%